Strategic activities to strengthen the tourism sector in the Heroic City of Huajuapan de León, Oaxaca - Flores Castillo, Lilia Alejandra (2020)
Usually, a tourist destination can be defined as that place with natural and cultural resources of great beauty; however, although locally there is no endowment of natural factors favorable to tourism, such as in the Heroic City of Huajuapan de León, Oaxaca, as there are different types of tourism, it is possible that, through innovation, attractive activities for leisure purposes can be generated, in a tourist setting where the different expectations of the user are met. Based on a qualitative study, the main objective of this paper is to present a series of strategic actions that encourage the development of tourist activities that generate an attractive place, and therefore, the strengthening of the tourist sector of the aforementioned city, whose implementation depends on the collective work between the community, the business sector and the government.